Computer System For Diagnostics of Mobile Machinery Transmission - G. L. Antipenko; A. N. Maximenko; B. M. Morgalik (Наука и техника)
A new method for diagnostics of mechanical transmissions of mobile machinery is proposed in the paper. The method presupposes an application of computing equipment and its purpose is to decrease labor-consumption of diagnostics procedure and increase diagnostics efficiency.The method is based on comparison of duration of impulse periods picked up at primary transducers which are installed at transmission input and output. A signal picked up at a flywheel ring gear is taken as a reference signal.While selecting clearances of one and then the direction in speed-up - braking transmission regime changes in number of reference impulses at output provide data on angular clearance value in every gearing. As data are supplied registration and processing of results and forecasting of residual resource are to be done with the help of a program on the basis of realized algorithms for every gearing.